Lightweight, secure, efficient, and dynamic scheme for mutual authentication of devices in Internet‐of‐Things‐Fog environment. (1st November 2022) - Jain, Usha; Pirasteh, Saied; Hussain, Muzzammil
Abstract: Security is a major challenge in the design and implementation of Internet‐of‐Things (IoT)‐Fog networks and it can be resolved by an efficient authentication mechanism. As the devices have limited resources like battery, processor and memory, any mechanism designed for IoT‐Fog has to be resource aware. In this paper, we proposed a lightweight, secure, dynamic, and efficient scheme for mutual authentication of devices in IoT‐Fog networks. In the proposed scheme, the devices obtain a primary security value from the cloud server and this acquired primary security value is used to authenticate them mutually. We used XOR operation, concatenation operation, one‐way hash function and symmetric key cryptography to accommodate resource constraint nature of devices. The proposed scheme has been analyzed for security formally using BAN logic and automated using Automated Validation of Internet Security Protocols and Applications & ProVerif tools and it is proved that the proposed scheme is secure from the known attacks. The comparative analysis of the proposed scheme with the existing schemes proved that it is better than existing schemes and its experimental analysis showed that it consumes 20%–30% less energy compared to existing schemes. Our proposed scheme is better with reference to security and efficient in respect of computation, communication, and storage overheads.